Achieving equivalence: a transnational curriculum design framework. Issue 4 (1st October 2016) - Clarke, Angela; Johal, Terry; Sharp, Kristen; Quinn, Shayna
Abstract: Transnational education is now essential to university international development strategies. As a result, tertiary educators are expected to engage with the complexities of diverse cultural contexts, different delivery modes, and mixed student cohorts to design quality learning experiences for all. To support this transition we developed a transnational curriculum design framework that synthesises knowledge about what impacts on curriculum design. This framework aims to help academic developers communicate complex educational concepts and foster international communities of practice. It guides cyclical implementation that is focused on achieving equivalent and quality educational outcomes for students regardless of their location across the globe.